Septate Uterus: Implications in Malpresentation and Infertility History - Sri Wahyu Maryuni; Cantika Anakita (Indonesian Journal of Obstetrics & Gynecology Science, 2026)
Introduction: A septate uterus is a congenital uterine anomaly linked to increased risks of infertility, recurrent miscarriage, and fetal malpresentation. Although often asymptomatic, it may significantly affect pregnancy outcomes. Early diagnosis and management are vital to reduce complications.Case Report: This case was conducted at Siak Hospital involving a 38-year-old G4P0A3 woman presenting with preterm labor. A partial uterine septum was identified during an emergency cesarean section. The patient had a history of multiple miscarriages. Ultrasound revealed a transverse fetal position with oligohydramnios, prompting cesarean delivery of a 1700-gram neonate. Both maternal recovery and neonatal progress were favorable.Conclusion: This case highlights the importance of individualized care in pregnancies complicated by uterine anomalies. While pre-conception surgical correction may improve outcomes, antenatal diagnosis requires close monitoring. Decisions regarding preterm termination depend on fetal presentation, amniotic fluid, and placental function. Imaging modalities support delivery planning. Although routine screening is not universal, it should be considered in women with recurrent loss or infertility. Multidisciplinary management is essential to optimize maternal and neonatal outcomes. Continued research is needed to establish standardized guidelines for managing pregnancies with septate uterus. AbstrakPendahuluan: Septum uteri adalah kelainan bawaan pada uterus yang berhubungan dengan peningkatan risiko infertilitas, keguguran berulang, dan malpresentasi janin. Meskipun sering tanpa gejala, kondisi ini dapat berdampak signifikan terhadap luaran kehamilan. Deteksi dan penanganan dini penting untuk mencegah komplikasi.Laporan Kasus: Laporan kasus ini dilakukan di RSUD Siak, pada seorang wanita G4P0A3 usia 38 tahun yang datang dengan persalinan prematur. Saat operasi sesar emergensi ditemukan adanya septum uterus parsial. Riwayat kehamilan menunjukkan keguguran berulang. Ultrasonografi menunjukkan posisi janin melintang dan oligohidramnion sehingga dilakukan tindakan sesar dengan bayi perempuan lahir seberat 1700gram. Pemulihan ibu dan bayi berjalan stabil.Kesimpulan: Kasus ini menekankan pentingnya tata laksana individual pada kehamilan dengan kelainan rahim. Koreksi bedah sebelum kehamilan dapat memperbaiki prognosis, namun jika terdiagnosis saat hamil, diperlukan pemantauan ketat. Keputusan terminasi prematur bergantung pada posisi janin, jumlah cairan ketuban, dan fungsi plasenta. Modalitas pencitraan canggih membantu perencanaan persalinan. Skrining rahim tidak wajib untuk semua wanita, namun perlu dipertimbangkan pada kasus infertilitas atau keguguran berulang. Pendekatan multidisiplin diperlukan untuk meningkatkan hasil ibu dan bayi. Penelitian lebih lanjut dibutuhkan untuk menetapkan panduan tata laksana yang baku.